SURGERY COMPLICATIONS IN REPRODUCTIVE WOMEN, THEIR INTERACTION WITH CYCLIC CHANGES IN GONADOTROPHIC AND STEROID HORMONES - F. Z. Mirsaeva (Креативная хирургия и онкология, 2017)
The article presents results of the study on the vegetative nervous  system  state, blood coagulation properties, immunologic indicators of blood and oral fluids during diverse phases of  the  menstrual cycle in reproductive women. Dependence of  surgery  complications development on cyclic changes in gonadotrophic and steroid  hormones has been shown.